A novel multi-drive electric vehicle system control based on multi-input multi-output PID controller - Gasbaoui Brahim; Nasri Abdelfatah (Serbian Journal of Electrical Engineering, 2012)
In-wheel-motor drive electric vehicle (EV) is an innovative configuration of the modern EV, in which each wheel is driven individually by an electric motor. The classical traction motor control called the Independent Machine Control Structure (IMCS) using a PID speed controller presents major inconveniences in modern EV safety, when the proposed control can not ensure stability of the EV with differing road topology and variations of speed. A new approach is proposed for a control of a two-in-wheel-motor drive EV, called the Maximum Control Structure MCS. This is based on a multivariable PID (MIMO-PID) strategy, which is employed to estimate the linear speed error of each of the two back driving wheels, when the error of each wheel is taken into account in the other speed control computations. Simulation results show that the new control system presents increased safety for the EVs compared with the IMCS strategy and can maintain the error slip rate within the optimal range, ensuring the stability of the vehicle either in a straight or a curved line.